Synergistic carcinogenesis of the nasopharyngeal microbiome and Epstein-Barr virus: mechanisms of metabolic reprogramming and immune evasion - Shen, Shasha; Li, Juan; Zheng, Sijia; Cui, Xue; Gou, Xiaoxia (Frontiers in Immunology, 2026)
Nasopharyngeal carcinoma (NPC) is strongly associated with Epstein-Barr virus (EBV) infection, but EBV alone is insufficient for tumorigenesis. Recent evidence suggests that the nasopharyngeal microbiome plays a critical, yet underexplored, role in NPC development. This review investigates the synergistic interaction between EBV and the nasopharyngeal microbiome, focusing on microbial dysbiosis and its role in NPC pathogenesis. We highlight significant microbial dysbiosis in NPC patients, characterized by an overgrowth of opportunistic pathogens such as Fusobacterium nucleatum and Porphyromonas gingivalis. These pathogens interact with EBV-infected epithelial cells, amplifying oncogenic signaling through the NF-κB and PI3K/AKT pathways. Crucially, we explore the “SCFA paradox,” where microbial short-chain fatty acids (SCFAs), typically beneficial, act as HDAC inhibitors that paradoxically trigger EBV lytic reactivation in B-cells. Additionally, the microbiome facilitates immune evasion through interactions between F. nucleatum Fap2 and the TIGIT receptor, in synergy with EBV’s LMP1 protein. These findings underscore the importance of the microbiome in NPC pathogenesis and highlight the potential for integrating microbial signatures into diagnostic tools. We conclude by discussing precision therapies, such as bacteriophage treatment, and emphasize the role of next-generation models—specifically Air–Liquid Interface organoids—as functional ‘patient avatars.’ These systems are essential for advancing personalized medicine, as they enable the functional validation of individualized microbial interventions that sequencing alone cannot predict.